Pre-primary school teacher training program in Kotebe University of Education: provision and policy implications - Abunu Arega Yismaw (Bahir Dar Journal of Education)
If someone plans to build a house, she/he needs to lay the foundation that supports the entire structure. A similar foundation is mandatory before a child enters primary school. Pre-primary education provides a stimulating environment for the physical, intellectual, linguistic, social, and emotional development of children. In that regard, this study explores the provision of the pre-primary teacher training program at the Kotebe University of Education. The research uses a qualitative case study. Data were gathered from the Ministry of education, Kotebe University of Education, and Addis Ababa city education bureau through interviews, observation, and document analysis. Six key informants were purposely selected, and a thematic data analysis technique was employed to analyze the qualitative data. The findings indicated that the pre-primary teacher training program is critically challenged by the shortage of trainers, financial and material constraints, inconclusiveness of the selection criteria of trainees’, overcrowded workshops, and absence of connections with social service-providing organizations. Regardless of policy interventions, the pre-primary school teachers’ qualification framework is not considered yet. Thus, the program requires the attention of every concerned stakeholder. Hence, the training college, the city education bureau, and the education planners need to prioritize the provision of quality training for pre-primary school teachers. The national quality framework of pre-primary teacher education should also be considered in order to measure the quality of training programs offered in multiple teacher training institutes.